Descriptions of the last instar larvae of two species of Davidius Selys, 1878 from Erhai Lake Basin, Yunnan, China (Odonata: Gomphidae) - Li, Guo; Yang, Guo-Hui (Zootaxa, 2025)
The last instar larvae of Davidius zallorensis Hagen in Selys, 1878 and Davidius davidii yunnanensis Yang & Davies, 1996 are described and illustrated for the first time from Erhai Lake Basin, Yunnan Province, China, based on the final stage larvae reared in laboratory; notes on their habitats are also provided. Differences among the larvae of this genus are discussed.